2011
DOI: 10.2486/indhealth.ms1207
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Respirable Particulates and Silica in and around the Stone Crushing Units in Central India

Abstract: Stone crushing unit workers suffer from particulate matters and respirable silica at work and in their residents nearby. The present study was undertaken to evaluate the area and personal exposure concentration of respirable particulate matters and silica in workplaces and in surrounding villages. PM 10 , PM 4 and PM 2.5 were considered for unit area measurement and PM 4 and PM 2.5 were considered for personal exposure measurements. The ambient PM 10 and indoor respirable particulate sampling and analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The results for RCS exposure values among crusher operators (78 μg/m 3 ) in this study are lower than the study by Amran et al (2017) , who found that in crusher operators in Malaysian quarries, the RCS exposure values were 91 μg/m 3 . However, Mukhopadhyay et al (2011) reported alarmingly high exposure levels to RCS among helper, loader, and feeder workers in the stone crushing facility in India, who found the values to be between 4510 μg/m 3 and 8140 μg/m 3 , respectively. A study by Kuo et al (2018) in Taiwan foundry workers in the sandblasting process identified the highest levels of both respirable dusts (520 μg/m 3 ) and RCS (27 μg/m 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results for RCS exposure values among crusher operators (78 μg/m 3 ) in this study are lower than the study by Amran et al (2017) , who found that in crusher operators in Malaysian quarries, the RCS exposure values were 91 μg/m 3 . However, Mukhopadhyay et al (2011) reported alarmingly high exposure levels to RCS among helper, loader, and feeder workers in the stone crushing facility in India, who found the values to be between 4510 μg/m 3 and 8140 μg/m 3 , respectively. A study by Kuo et al (2018) in Taiwan foundry workers in the sandblasting process identified the highest levels of both respirable dusts (520 μg/m 3 ) and RCS (27 μg/m 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…(32) Similar results for airborne respirable quartz were obtained in areas of a stone crushing mill in a pilot project in India after the installation of a dust collection system. (33) Dry dust collection systems if adequately designed may be feasible where mining cooperatives have been formed or where centralized ore processing can be organized by the miners.…”
Section: Opportunities For Crystalline Silica Dust Reductionmentioning
confidence: 99%
“…Several studies have documented high to very high levels of mineral dust in worksites-and also the surrounding environment-where stones or rocks are crushed or milled using various types of mechanical crushers to produce aggregates for use in the construction of roads and buildings [1][2][3][4][5][6]. In these publications, the main emphasis was on the health risks associated with high exposures to free crystalline silica, i.e., mainly quartz, the content of which depends on the nature of the materials that are being crushed.…”
Section: Introductionmentioning
confidence: 99%